Accurate and Precise Elemental Abundance of Zinc inReference Materials by an Isotope Dilution MassSpectrometry TIMS Technique - Ghidan, Osama; Loss, Robert (Wiley-Blackwell Publishing, Inc., 2010)
A thermal ionisation mass spectrometric technique enabled the abundance of Zn in geological and biological reference materials and water samples to be measured by double spiking isotope dilution mass spectrometry enriched in the 67Zn and 70Zn isotopes. In the past, thermal ionisation mass spectrometry proved to be difficult for low-level zinc isotopic measurements. The size of Zn samples used for isotopic determination, in particular the biological RMs, represents an important breakthrough. These results represent the most accurate and precise concentrations measured for Zn in these samples. The maximum fractional uncertainty was that for TILL-3 (2%), while the minimum fractional uncertainty was 0.7% for both BCR-1 and W-2. The inhomogeneity of Zn in HISS-1 was revealed while other reference materials appeared homogeneous at the 95% confidence uncertainty. The certified concentration of Zn in HISS-1 and IMEP-19 by their producers are 28% and 3.8% higher than the values measured in this work. These are the first Zn concentration measurements in these materials by the isotope dilution-TIMS technique, except for BCR-1, NIES No 9 and IMEP-19. Reducing the blank enabled accurate measurement in water at the ng g-1 level demonstrating the applicability of the technique for low-level Zn samples.